Prevalence of skin disorders in primary and secondary school age children in Canakkale, Turkey: a community-based survey - Uludağ, Aysegul; Kılıc, Sevilay Oguz; Isık, Selda; Ertekin, Yusuf Haydar; Tekin, Murat; Cevizci, Sibel; Ogretmen, Zerrin; Topaloglu, Naci; Sahin, Erkan Melih; Cıbık, Birol (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Skin lesions may be of dermatological importance, affect appearance, and cause problems communicating with peers and may be especially more significant in childhood. Aim :Information on the prevalence of pediatric dermatoses in Western Turkey. This study was aimed to define the existing data. Material and methods : A cross-sectional study was conducted in Canakkale, Turkey, in September-December 2013. It involved 1,957 students from five randomly selected primary and secondary schools. Each student was interviewed for age, gender, and family history, and a dermatologic examination was performed by a dermatologist. Data were coded and analyzed. Results :Of the students, 79.9% revealed at least one dermatosis. The most common disease was benign neoplasms (76%), followed by pigmentary disorders (26.8%), and xerosis (5.8%). In primary schools, the acquired melanocytic nevus, hypopigmented macule, and xerosis; in secondary school the acne was statistically significantly more common. Acne and xerosis was more common in girls, and pityriasis alba was statistically more common in boys. Students who had at least one dermatosis were positively correlated with monthly income. Conclusions :In Turkish school age children, the prevalence of dermatosis is 79.9%. It may be due to not using preventive means for adequate protection from the sun and other environmental factors. Infectious dermatosis and atopic dermatitis are rare and it may depend on the adequacy of public health work.